Appropriate Timing and Type of Physical Training in Patients with COVID-19 for Muscle Health and Quality of Life: A Systematic Review - I. Gusti Putu Suka Aryana; Siti Setiati; Ivana Beatrice Paulus; Dian Daniella (Journal of Nutrition and Metabolism)
Physical activity is beneficial to modulate immune system function and has inverse relationship to ARDS linked with SARS-CoV-2. Physical activity consists of daily activity and physical training. Studies regarding effect of physical training on patients with COVID-19 are controversial. This systematic review aims to investigate physical training on muscle health and QOL in patients with COVID-19. The literature review was carried out using keywords: (Exercise) AND (COVID) AND (Muscle) AND (Observational Study) in several databases of PubMed and Cochrane Central Register of Controlled Trials (CENTRAL). All references were reviewed using critical appraisal Newcastle Ottawa Scale (NOS) and Centre for Evidence-Based Medicine (CEBM) checklist. The studies were subsequently screened for reporting exercise, muscle, and COVID-19. The descriptions of the extracted data are guided by Preferred Reporting Items for Systematic Reviews (PRISMA) statement with GRADE approach. This study is registered in PROSPERO: ID CRD42021295188. Six studies pooled and entered review synthesis. Studies were reviewed using critical appraisal by NOS and CEBM. Two clinical trial studies and four observational designs were selected. Our result showed physical training improved patients’ outcomes in the acute phase, critical phase, and post-COVID-19 phase. Multiple types of physical trainings were suggested by those studies, and most of them showed beneficial effects to patients with COVID-19 in different phases. The level of evidence by GRADE was downgraded, and further investigations are needed to establish guidelines and strong recommendation for a specific stage of COVID-19.